PENGARUH KARAKTERISTIK ENTREPRENEURSHIP, PERAN GENDER, PEKERJAAN ORANG TUA, DAN DUKUNGAN AKADEMIK TERHADAP MINAT KEWIRAUSAHAAN MAHASISWA - Rozi, M Fatkhur; Solekah, Nihayatu Aslamatis (IQTISHODUNA, 2015)
This study aimed to determine the effect of entrepreneurship characteristics, gender roles, parents’occupations, and academic support for student entrepreneurial intentions. This study is quantitative studyaimed to test the effect of all variables simultaneously and partially. The research used purposive sampling ofUIN Maulana Malik Ibrahim students from six faculties which consist of FITK, Faculty of Shariah, Faculty ofHumanities, Faculty of Economics, Faculty of Psychology and Faculty of Science and Technology with 250respondents. The results of this study showed that the characteristics of entrepreneurship, gender roles, theparents’ occupations, and academic support simultaneous effect on student intentions in entrepreneurship.There are two variables that partial effect on the variable of intentions student entrepreneurship characteristicsand role of gender. The other two variables which are the parents’ occupation and academic support are notpartial effect on student interest in entrepreneurship. Characteristics of entrepreneurship has a dominantinfluence on the intentions of the student entrepreneurship